The Validity of The Deed of Sale and Purchase and the Deed of Granting Rights and Legal Consequences for the Winner of the Auction Based on a Mock Agreement - Anggun Riska Amalita; Sulistyandari Sulistyandari; Tri Lisiani Prihatinah (Journal of Social Research, 2024)
The validity of a covenant must meet 4 conditions, namely an agreement that binds him, the ability to make an agreement, about a certain matter, and a lawful cause. One example is in the Supreme Court Decision Number 655 K / Pdt / 2014 and Review Decision Number 636 PK / Pdt / 2016, there are differences in decisions regarding the Deed of Sale and Purchase and the Deed of Granting Rights of Dependents on the basis of a mock agreement. This study aims to analyze the validity of the sale and purchase deed and the deed of granting dependent rights as well as the legal consequences for the auction winner based on a mock agreement. The research method used is normative juridical, with a statutory approach, a conceptual approach, and a case approach. The data used in this study are secondary data obtained from literature studies. The results of the research obtained are the Validity of the Deed of Sale and Purchase of land rights based on receivables in the Supreme Court Decision Case Number 655 K / Pdt / 2014 states that the Sale and Purchase Deed made by PPAT is invalid and null and void. This is because in making the Deed of Sale and Purchase by PPAT based on the temple agreement made by a Notary, it does not meet the material requirements of an authentic deed, namely the non-fulfillment of the elements of a halal cause as stipulated in Articles 1335 and 1337 of the Civil Code, thus it also cancels the crossing out of the name in the land certificate from the Plaintiff to the Defendant carried out by BPN. In the decision of Review Decision Number 636 PK / PDT / 2016 stated that the Deed of Sale and Purchase and Deed of Granting Rights of Dependents were valid and there was no pretend agreement. The winner of the auction based on the Minister of Finance Regulation No. 93/2010 on auction implementation guidelines is the buyer who submits the highest bid and is certified as the winner of the auction by the Auction Officer. Article 41 paragraph (1) of Government Regulation No. 24/1997 on land registration explains that the transfer of land rights through transfer of rights by auction can only be registered if proven by quotation of auction minutes made by auction officials.